An Overview of the Importance of DEM Resolution in Soil Erosion Assessment - Kariminejad, Narges (2024)
Soil erosion is a geomorphic process that can cause hazards and socioeconomic losses. These processes occur through subsurface and overland flows. We conducted a literature review on the importance of digital elevation model (DEM) resolution in soil erosion assessment. This review article presents the state of the art regarding the importance of the resolution of DEM in soil erosion assessment. It explains why DEM resolution is important for understanding how erosion is assessed. Further research is needed, however, to better explore the connectivity and morphology of soil erosion, including its subsurface watershed and behavior, as well as several challenges faced in using DEMs for soil erosion analysis. Understanding quantitative variables that initiate soil erosion and considering multihazard assessments can aid in developing techniques and assisting decision makers in designing accurate systems. Exploring soil erosion also needs improved high-resolution tools (e.g., unmanned aerial vehicles) that enable more reliable predictions of soil erosion and the detection of erosion-affected regions. Addressing these knowledge gaps will enhance our understanding of subsurface and surface erosion, contribute to a better understanding of landscape evolution, and further improve the development of effective strategies and techniques for soil erosion control. The research findings are highly transferable in diverse geographical contexts worldwide.